Selective glucocorticoid receptor (type II) antagonists prevent weight gain caused by olanzapine in rats - Belanoff, Joseph K.; Blasey, Christine M.; Clark, Robin D.; Roe, Robert L. (European journal of pharmacology, 2011)
The use of antipsychotic medication has consistently been associated with serious side effects including weight gain and metabolic abnormalities. Strategies for mitigating these side effects have been tested, yet effective interventions have not been identified. The current study tested whether two recently identified selective glucocorticoid receptor antagonists would prevent weight gain induced by the antipsychotic olanzapine. Female Sprague–Dawley rats fed a normal chow diet were randomized (n = 10 per group) to receive one of the following for 18 days: vehicle, olanzapine plus vehicle (2.4 mg/kg), olanzapine plus CORT 112716 (20 mg/kg), olanzapine plus CORT 112716 (60 mg/kg), olanzapine plus CORT 113083 (20 mg/kg), or olanzapine plus CORT 113083 (60 mg/kg). Rats receiving olanzapine plus CORT 112716 (60 mg/kg) or olanzapine plus CORT 113083 (60 mg/kg) gained significantly less weight than rats receiving only olanzapine. Both glucocorticoid receptor antagonists significantly attenuated the weight gain induced by olanzapine in a dose dependent manner. Differences in weight gain were not attributable to decreased food intake.